ANALISIS STRUKTUR KRISTAL LITHIUM OKSIDA DAN NIOBIUM PENTAOKSIDA DENGAN XRD - Nadia Septiani; Irzaman Irzaman (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
Lithium oxide and niobium pentaoxide are materials which are used as lithium niobate. XRD result showed that lithium oxide has anti-flourite (cubic) structure with lattice parameter of a is 4.617 Å. Niobium pentaoxide has monoclinic structure and lattice parameter of a is 18.5070 Å, b is 7.7679 Å and c is 17.5994 Å. Keywords: crystal structure ,lattice parameter, lithium oxide, niobium pentaoxide, XRD.